2006
DOI: 10.3892/or.16.5.1123
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the diagnosis of dysplasia in ulcerative colitis by dynamic telepathology

Abstract: Abstract. Telepathology (TP) is the practice of evaluating pathology cases by the digital transmission of diagnostic slides as either static pictures (static TP) or by a continuous flow of pictures from a robotic microscopy (dynamic TP). The diagnostic efficacy of dynamic TP-based consultation services has not been widely tested. Dysplasia arising in association with chronic ulcerative colitis (CUC) is, at present, the most important marker for an increased risk of malignancy in patients with this disease. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Previously reported studies describing the measurement of pathologist interobserver agreement when viewing other surgical pathology specimen types using conventional light microscopy or digital images (either static or dynamic) show highly variable levels of agreement, ranging from essentially perfect [19] to fair [20]. Regardless of the specific Îș statistics calculated, measurements of interobserver agreement that are essentially no better for microscopic slides compared to digital images support the validity of digital images for use in telepathology-based consultation.…”
Section: Discussionmentioning
confidence: 89%
“…Previously reported studies describing the measurement of pathologist interobserver agreement when viewing other surgical pathology specimen types using conventional light microscopy or digital images (either static or dynamic) show highly variable levels of agreement, ranging from essentially perfect [19] to fair [20]. Regardless of the specific Îș statistics calculated, measurements of interobserver agreement that are essentially no better for microscopic slides compared to digital images support the validity of digital images for use in telepathology-based consultation.…”
Section: Discussionmentioning
confidence: 89%
“…72,80 Because of low interobserver agreement regarding dysplasia, especially in the context of inflammation, 2 expert gastrointestinal pathologists should confirm dysplasia. 81 There is no pathognomonic appearance in IBD, making endoscopic surveillance difficult. DALMs may appear as a single polypoid mass, a plaque-like lesion or multiple polyps.…”
Section: Colitis-associated Neoplasiamentioning
confidence: 99%
“…For instance, Odze et al [18] have shown that, although there is no significant difference in the degree of interobserver variability in telepathology diagnosis of dysplasia in ulcerative colitis using fluid images over glass slides, when participants were given the glass slides to review, most of the expert gastrointestinal pathologists (51%) changed their diagnosis, and a majority of these cases (61%) downgraded the degree of dysplasia from the original telepathology diagnosis. The high interobserver variability is well documented in issues of gastrointestinal dysplasia.…”
Section: Malpractice and Liabilitymentioning
confidence: 99%